(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The aim of the research is to identify the losses resulting from the terrorist operations and then find a proposed accounting treatment for the losses resulting from the terrorist operations and to indicate their impact on disclosure in the financial statements by reviewing the international standards and local rules and the unified accounting system and not dealing with these losses, Of the financial statements and therefore adversely affect the accounting disclosure as well as the weak commitment of economic units to apply the requirements of accounting measurement and disclosure of losses of terrorist operations in a manner consistent with local and international standards to achieve the Reliability in the financial statement.